The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1007/s10103-013-1366-6
|View full text |Cite
|
Sign up to set email alerts
|

Temperature rise during experimental light-activated bleaching

Abstract: The purpose of this study was to evaluate the surface and intrapulpal temperatures after treatments with different bleaching gels subjected to different types of light activation. A K-type thermocouple and infrared thermometer were used to measure the temperature increase during the 15- or 30-min treatment period. Light-emitting diode with a center wavelength of 405 nm (LED405), organic light-emitting diode (OLED), and femtosecond laser were tested and compared to ZOOM2. The tooth surface was treated with five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 27 publications
0
22
0
4
Order By: Relevance
“…8,9 It is important to state that the type of LED-laser models available, with different delivery systems and power light sources, coupled with the diversity of catalyzing agents, makes it difficult to make a comparison with other studies. 15,16,18,20,22 Nevertheless, it is important to emphasize the need for further research into the use of hybrid light sources in tooth bleaching. Therefore, further studies of the use of bleaching agents in lower concentrations coupled with hybrid sources, and the use of separate therapeutic laser treatment are required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 It is important to state that the type of LED-laser models available, with different delivery systems and power light sources, coupled with the diversity of catalyzing agents, makes it difficult to make a comparison with other studies. 15,16,18,20,22 Nevertheless, it is important to emphasize the need for further research into the use of hybrid light sources in tooth bleaching. Therefore, further studies of the use of bleaching agents in lower concentrations coupled with hybrid sources, and the use of separate therapeutic laser treatment are required.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,6,8 A possible reason why we did not find different results between the groups is probably because the therapeutic laser that is present in these hybrid sources does not come into direct contact with the target tissue. 13 One should also consider the barrier formed by the colored HP gel can minimize the density of the power in the target tissue and maximize light reflection, 6,16,17,19,22 significantly decreasing the absorption of laser by the tissue (dental pulp), which means that the therapeutic action of the laser is reduced. 13 The fact that the hybrid LED-laser source has three laser outputs, and that laser light is not collimated, means that the light may, therefore, not reach the target properly.…”
Section: Discussionmentioning
confidence: 99%
“…Com base nesta revisão de literatura, o uso da luz no clareamento dental apenas aumenta a velocidade de reação da substância, uma vez que se tem o mesmo efeito do gel clareador sem o seu uso, mas foi observado que, se aplicado por muito tempo ou por fontes de luz inadequadas, pode induzir a comprometimento intrapulpar 12,13 . Além disso, verifi cou-se que a sensibilidade pós-procedimento era sempre maior 14 .…”
Section: Discussionunclassified
“…In a study by Luk et al (16) the application of infrared laser, CO2 laser, halogen lamp and argon laser in combination with 35% hydrogen peroxide gel and 10% carbamide peroxide gel caused significant temperature increase inside the pulp chamber and on the tooth surface. Klaric et al (34) found that the ZOOM2 light source led to the largest increase in mean pulpal and tooth surface temperatures of 21.1 and 22.8 °C, followed by focused femtosecond laser which increased the pulpal and surface temperatures by up to 15.7 and 16.8 °C. Also, the effect of an intact pulpal circulation or simulated blood flow is able to dissipate some of the applied heat before pulpal cells are damaged (40,41).…”
Section: šAntak I Surmentioning
confidence: 99%
“…According to the available literature, the use of the light activation in conjunction with bleaching gels generates higher intrapulpal temperatures (34)(35)(36). In the present study, during the bleaching procedure, the heat generated by APP jet was measured on the surface of the treated samples and in all cases it did not pass 33˚C.…”
Section: šAntak I Surmentioning
confidence: 99%